PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI DAN RESERVASI ONLINE PADA SLIMMY & BEUATY SPA - Leman, Thomas; Adipranata, Rudy; -, Liliana (Jurnal Infra, 2013)
Slimmy and Beauty Spa is a company which involve and offer a Modern Spa Business. Main target especially woman - middle up class in Surabaya Area. The speciality which differentiate Slimmy & Beauty Spa from other competitor is a